From Auster to Apache the history of 656 Squadron RAF/AAC 1942-2012 - Warner, Guy (Pen & Sword Aviation, 2013)
656 Squadron celebrated its 70th Anniversary on 31 December 2012. Over the intervening years, the Squadron has served with great distinction in India, Burma, Java, Malaya, Borneo, Hong Kong, the UK, the Falkland Islands, Bosnia, Kosovo and, most recently, in Afghanistan. This is 656's story, told in full and for the first time.656 Squadron's story is a diverse one, characterized by active deployment in a range of wartime theaters.